Inspection of Pipe Welds Using the Radiogrphy Method with the Double Wall Double Image Technique - Aulia Riska; Syukran Syukran; Hasrin Lubis (Politeknik Negeri Lhokseumawe, 2022)
Inspection of 900 angle pipe welds using the Radiography method with an Ir.192 source with a capacity of 150 Curie while operating 56 curies using the Double Wall Double Image Technique Case study at (PT. Sinar Mas, Riau). Errors and inaccuracies in timing result in the resulting image being damaged, not meeting radiographic film acceptance quality standards. irradiation (exposure time). The purpose of this paper is to be able to calculate the exposure time using computation, and to know the type of defects in the welding and there are significant undercutting defects that require repair or re-welding and are declared rejected by the radiographer. The results of the exposure time calculation between the calculations of several processes have a relatively large time difference, this is because they do not follow the curve value. In the end it can be concluded from the results of the film is very influential on the exposure time. Based on this, the resulting software can be declared in accordance with field conditions